Ecosystem size shapes antipredator trait evolution in estuarine threespine stickleback. Issue 12 (2nd September 2020) - Wasserman, Ben A.; Paccard, Antoine; Apgar, Travis M.; Des Roches, Simone; Barrett, Rowan D. H.; Hendry, Andrew P.; Palkovacs, Eric P.
Abstract : Ecosystem size is known to influence both community structure and ecosystem processes. Less is known about the evolutionary consequences of ecosystem size. A few studies have shown that ecosystem size shapes the evolution of trophic diversity by shaping habitat heterogeneity, but the effects of ecosystem size on antipredator trait evolution have not been explored. Ecosystem size may impact antipredator trait evolution by shaping predator presence (larger ecosystems have longer food chains) and habitat complexity (larger ecosystems may have more diverse habitat structure). We tested these effects using threespine stickleback from bar‐built estuaries along the Central Coast of California. These stickleback populations are polymorphic for Ectodysplasin‐A ( Eda ), a gene that controls bony lateral plates used as antipredator defense. We inferred Eda genotypes from lateral plate phenotypes and show that the frequency of the complete (C) allele, which is associated with greater number of lateral plates, increases as a function of ecosystem size. Predator presence and habitat complexity are both correlated to ecosystem size. The strongest proximate predictor of Eda allele frequencies was the presence of predatory fishes (steelhead trout and sculpin). Counter to expectations, habitat complexity did not have a strong modifying effect on Eda allele frequencies. Our results point to the importance of ecosystem size for determining predator presence as being the primary pathway to evolutionary effects. Ecosystem size has received much attention in ecology. Our work shows that it may be an important determinant of adaptive evolution in wild populations.